'Man of the Mountain': Seeing Jefferson at Monticello. (24th April 2019) - Tietze Larson, Victoria S.
Abstract: Jefferson's 'retirement' at Monticello – built, exceptionally for a Virginia plantation house, on top of a mountain – provided the requisite audience for a carefully fashioned self‐image. Its inspiration lay in classical descriptions of country living and mountain‐top villas, which had been appropriated by eighteenth‐century polite literature as part of the imaginary of the British landed gentleman. Although conceived as part of a process of righteous self‐distancing from Europe, Jefferson's retirement nevertheless situated him in a cosmopolitan, elite and genteel company, a fact that complicated his quest to meet republican ideals.